Myeloid Cell Crosstalk Regulates the Efficacy of the DNA/ALVAC/gp120 HIV Vaccine Candidate - Vaccari, Monica; Fourati, Slim; Brown, Dallas R.; Silva de Castro, Isabela; Bissa, Massimiliano; Schifanella, Luca; Doster, Melvin N.; Foulds, Kathryn E.; Roederer, Mario; Koup, Richard A.; Sui, Yongjun; Berzofsky, Jay A.; et al. (Frontiers in Immunology, 2019)
The DNA-SIV + ALVAC-SIV + gp120 alum boost vaccine regimen induces innate monocyte memory immunity via inflammasome activation, high levels of IL-1 production, emergency myelopoiesis, and the egress of CXCR4+CD14+ pre-monocytes from bone marrow. Vaccine-associated innate monocyte memory is itself associated with decreased risk of SIVmac251 acquisition and decreased T-cell activation. Interestingly, this regimen also induced CD16+ monocytes that are instead associated with an increased risk of SIV acquisition. Because IL-1 also promotes the propagation of monocyte-derived suppressor (M-MDSC)-like cells, we extended our analysis here to include them. We found that engagement of M-MDSC-like cells by the DNA prime was associated with the frequency of CD14+ classical monocytes, and with the induction of arginase activity that inversely correlated with functional SIV-specific CD8+ T cells. Furthermore, arginase activity positively correlated with the frequency of CD16+ monocytes and nitric oxide (NO) signaling. Accordingly, M-MDSC frequency, arginase activity, and NO were associated with an increased risk of SIVmac251 acquisition. DNA vaccination thus induces protective immunity by engaging three subsets of myeloid cells, M-MDSCs, CD14+ innate monocyte memory, and CD16+ monocytes. The full characterization of the immunological space created by myeloid cell crosstalk will likely provide clues to improve the efficacy of HIV vaccine candidates.